The evaluation of project management practices relationship with the project performance outcome of reconstruction development programme (RDP) and subsidy housing - Tseladikae, Tshepo (Vaal University of Technology, 2022)
As citizens migrate from rural to urban locations, coupled with the population growth in South Africa, housing supply remains an imperative task. Regarding this migration and housing need, the South African government, shortly after the dawn of democracy, has been providing housing to its previously disadvantaged citizens due to the apartheid government. The housing typology that the government delivers to its citizens is the Reconstruction Development Programme (RDP) and subsidy housing. The construction industry has difficulties achieving satisfactory project performance, especially with the current delivery of the Reconstruction Development Programme and subsidy housing projects in South Africa. Most housing projects are never completed satisfactorily as contractors either abandon the project or deliver it late. They incur cost overruns and poor quality, making it an expensive and wasteful process for the beneficiaries and the government. As a result, this dissertation investigated the relationship between project management practices (PMPs) usage and project performance outcomes for the RDP and subsidy housing in South Africa. The research design was quantitative in nature, using primary data and the data were analysed using the IBM Statistical Package for Social Sciences (SPSS). The main statistical parameters used to present and analyse data results were mean score, correlation and factor analysis. The researcher used a questionnaire survey to gather the primary data and address the objective of this study, which is a deductive research approach. A convenience non-probability sampling method was used for sampling the participants. The questionnaire was administered to Gauteng-based small and medium contractors undertaking the RDP and subsidy housing projects. A total of 116 questionnaires were returned for analysis. However, one questionnaire was removed from further analysis because it was a large contractor as per the Department of Trade and Industry definition. As per the results, the majority of the respondents were males; 14 percent were females and 86 percent were males. The majority had a minimum qualification of a diploma, which represented 50.9 percent. The challenges faced by contractors were ranked using the mean score. The findings indicated that late payment of contractors was deemed a significant challenge. Furthermore, factor analysis established that the challenges stated were a three-factor model, categorised as project management, environmental and financial factors. The 86 PMPs identified in the literature were analysed using exploratory factor analysis (EFA). The results from the EFA established a ten-factor model in line with the theory of the knowledge areas of the Project Management Body of Knowledge (PMBOK). The mean score was performed to determine the usage level and results showed that one project management practice, namely a bar chart, was used every time in the RDP and FLIP housing projects (mean = 4.25 and Std. Deviation = 0.77), ranking first. Eighty-two other PMPs were used almost every time, as their mean scores were in the range of 3.41 to 4.20. On the contrary, Pareto, flow chart and fishbone were almost never used as they were in the range of 1.81 to 2.60. The final part of the results determined the performance outcome of the project and the relationship between the usage of the PMPs and the project performance outcome. The identified performance outcome measures were analysed using EFA and three components of the performance outcome measures were identified: compliance and financial performance, contractor process and employee satisfaction and contractor process and employee satisfaction. Spearman’s rho correlation, which is non-parametric, was used to evaluate the relationship between the three project performance outcomes and the 10 PMPs. From the results, the hypotheses tested indicated that nine of the PMPs, namely scope, schedule, cost, quality, integration, stakeholder, resources, communication and risk management, significantly correlate with one of the three project performance outcomes. However, the procurement management practice established no significant correlation with any of the three project performance outcomes. In conclusion, PMP has a relationship with the project outcome and each area of project management affects a different aspect of performance; for instance, cost management practices showed a relationship with compliance and financial performance component whereas stakeholder was customer performance component, the following recommendations were made: Relevant PMPs found to correlate with the performance outcomes of the project should be made compulsory for every RDP and subsidy housing project; qualified personnel should be employed to care for a project management role and not be a passive role given to anyone; training in PMPs should be compulsory for all those involved in the construction of RDP and subsidy housing projects.
M. Tech. (Department of Civil Engineering and Building, Faculty of Engineering and Technology), Vaal University of Technology.
Keywords: Construction industry; Project management practices; Project performance challenges; Project performance outcome; Reconstruction and development programme; Small and medium enterprise; Subsidy housing; Dissertations, Academic -- South Africa.; Project management -- South Africa.; Reconstruction and Development Programme (South Africa).; Housing subsidies -- South Africa.; Contractors -- South Africa.